2019
DOI: 10.1097/ju.0000000000000137
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Prostate Cancer Germline Genetics into Clinical Practice

Abstract: Purpose: Until recently the role of germline genetics in prostate cancer care was not well defined. While important questions remain, we reviewed the current understanding of germline genetic alterations related to prostate cancer. We discuss the clinical implications for genetic counseling, genetic testing, early detection and treatment in men with these mutations. Materials and Methods: We searched PubMedÒ for English language articles published since 2001 with the key words "germline mutations," "BRCA," "fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 47 publications
1
55
0
1
Order By: Relevance
“…Multiple mass spectrum-based studies have identified a diverse number of acetyl-lysine sites on MMR proteins (MSH2, MSH3, MSH6, MLH1, and PMS2) (17,18). Dysregulation of MSH2 has been pointed out to generate genomic instability, resulting in the development of prostate (19), colorectal (20), and hepatic (21) cancers. A previous study found that the levels of MutSα were controlled through MSH2 acetylation in vivo.…”
Section: Mismatch Repairmentioning
confidence: 99%
“…Multiple mass spectrum-based studies have identified a diverse number of acetyl-lysine sites on MMR proteins (MSH2, MSH3, MSH6, MLH1, and PMS2) (17,18). Dysregulation of MSH2 has been pointed out to generate genomic instability, resulting in the development of prostate (19), colorectal (20), and hepatic (21) cancers. A previous study found that the levels of MutSα were controlled through MSH2 acetylation in vivo.…”
Section: Mismatch Repairmentioning
confidence: 99%
“…These findings underscore the need to optimise early detection strategies in men with a high genetic risk-particularly germline mutations in BRCA2-with early screening performed before age 45 or, in patients with a family member diagnosed with cancer, 10 years before the age of diagnosis. In addition, the PSA threshold in these patients should be lowered to 2.5 ng/dL and other biomarkers should be assessed as part of the diagnostic process [66].…”
Section: Biomarkers Of Susceptibilitymentioning
confidence: 99%
“…Significant factors contributing to the underutilization of genetic testing are likely the lack of clear guidelines regarding how the results should be used to alter management and the shortage of genetic counselors. However, improvements are continuously being made [84][85][86]. Still, there remains a significant amount of work needed to better determine which patients should undergo genetic testing, the timeframe during which testing should be conducted, what techniques should be used, and how the information can be utilized to better serve patients and their families.…”
Section: Genetic Counseling Overviewmentioning
confidence: 99%